Gaya Persuasif Dalam Penerapan Logos Pada Konten Tiktok @vmuliana Tips Berkarir Ditinjau Dari Perspektif Aristoteles - Listiyani, Feni; Muliawati, Lintang (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
his study aims to describe the persuasive style used by TikTok celebrity Vina Muliana in providing career tips for people on social media, especially TikTok. This research is a qualitative research using qualitative descriptive method. Research data and sources are in the form of career tips videos uploaded by Vina Muliana on her personal TikTok account named @vmuliana. The results of this study found 35 data on the application of logos in TikTok celebrity Vina Muliana in persuading the publik in each of her uploaded videos by presenting facts and opinions. Vina Muliana also uses persuasive sentences to strengthen her opinion. Based on research data, Vina Muliana often brings up facts in the form of tricks to get a good career.